2014
DOI: 10.1175/jpo-d-14-0012.1
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy-Driven Coastal Currents off Oregon during Fall and Winter

Abstract: During fall/winter off the Oregon coast, oceanographic surveys are relatively scarce because of rough weather conditions. This challenge has been overcome by the use of autonomous underwater gliders deployed along the Newport hydrographic line (NH-Line) nearly continuously since 2006. The discharge from the coastal rivers between northern California and the NH-Line reach several thousands of cubic meters per second, and the peaks are comparable to the discharge from the Columbia River. This freshwater input cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 55 publications
(76 reference statements)
1
34
0
Order By: Relevance
“…Cross‐shore glider transects recorded many appearances of the CRP through the 7 years of study, however, here we only present results from the glider trajectories that are concordant with clear MODIS nLw(555) fields identifying both the presence and absence of the CR plume. The MODIS imagery also revealed that some events with low‐salinity water were consistent with the signal from the small local rivers of central Oregon [ Mazzini et al ., ] under upwelling conditions and mostly during early spring. Thus, glider data suggesting the presence of the CR plume but not supported by a clear MODIS image showing the presence of the CR plume were discarded in order to avoid the inclusion of glider data under the influence of these small rivers.…”
Section: Resultsmentioning
confidence: 98%
“…Cross‐shore glider transects recorded many appearances of the CRP through the 7 years of study, however, here we only present results from the glider trajectories that are concordant with clear MODIS nLw(555) fields identifying both the presence and absence of the CR plume. The MODIS imagery also revealed that some events with low‐salinity water were consistent with the signal from the small local rivers of central Oregon [ Mazzini et al ., ] under upwelling conditions and mostly during early spring. Thus, glider data suggesting the presence of the CR plume but not supported by a clear MODIS image showing the presence of the CR plume were discarded in order to avoid the inclusion of glider data under the influence of these small rivers.…”
Section: Resultsmentioning
confidence: 98%
“…Deploying gear in the ocean involves some risk, as described for gliders by Brito et al (2014), whose view is based on many users new to gliders and is therefore rather bleak. My opinion is that more experienced glider operators have better performance, as must be the case for the glider programs that have been gathering data continuously for several years , Perry et al 2008, Todd et al 2011a, Pierce et al 2012, Pelland et al 2013, Mazzini et al 2014, Johnston & Rudnick 2015. The optimistic view is 10 August 2015 14:1 that ocean scientists willing to make an investment can approach the performance of experienced glider operators.…”
Section: Discussionmentioning
confidence: 99%
“…Davis (2010) used gliders equipped with ADCPs to show that the return flow is just beneath the surface wind-forced Ekman layer, implying that the heat flux is less than what would be expected if the return flow extended to the bottom. Sustained observations off Oregon have elucidated the buoyancy-driven currents associated with river discharge (Mazzini et al 2014). Timmermans & Winsor (2013) used two glider missions in the Chukchi Sea to examine the submesoscale horizontal structure in the surface layer.…”
Section: The Mesoscale and Submesoscalementioning
confidence: 99%
“…The assumption of geostrophic balance has been widely used in the literature to estimate along‐shelf baroclinic transport in river plumes, both from numerical model results (e.g., Fong & Geyer, ; Moffat & Lentz, ; Pimenta & Kirwan, ; Pimenta et al, ) and observations (e.g., Chant et al, ; Chant et al, ; Geyer et al, ; Mazzini et al, ). Pimenta et al () provided a thorough discussion of scalings to estimate plume baroclinic transports under the assumption of geostrophic balance.…”
Section: Discussionmentioning
confidence: 99%